"She Gave us Family Life": Vietnamese Immigrant Families and their Czech Nannies Redefining Relatedness - Souralová, Adéla (Lidé města, 2013)
Vietnamese families in the Czech Republic often recruit Czech women to look after their children. Put in the context of the dominant scholarship, this is quite a unique case of care work in which the employers are immigrants, while the employees are women of the host country. At the same time, it is an exceptional child care solution in the context of the Czech Republic, where only 1-2% of the population seek individual private child care. Drawing upon qualitative research conducted with Czech nannies, Vietnamese mothers, and their children, the article interprets the experience of Vietnamese immigrants with paid child care as an outcome of the post-migratory redefinition of family relations. In so doing, the paper demonstrates how family ties and child care arrangements are negotiated vis-à-vis the new life in the host country, where the different "normal caring biographies" are supported by the common-sense understanding of what care and/or mothering should be, by social policies, and by everyday practice. I argue that recruitment of the nannies is an essential part of these negotiations. I respond to the following questions: What is the role of delegated child care in post-migratory family arrangements? What are the motivations for and consequences of recruiting Czech nannies in the context of Vietnamese immigrants' family lives? In my paper I put forward the thesis that the post-migratory challenges of family life lead to the recruitment of nannies, which further challenges the family lives of both nannies and immigrants. The article focuses both on the negotiations which result in hiring the nanny and the negotiations originating in the recruitment of Czech nannies.